2013
DOI: 10.3372/wi.43.43119
|View full text |Cite
|
Sign up to set email alerts
|

Contributions to the flora of Albania, 4

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Several new species have been described recently (e.g. Niketić and Stevanović 2007;Schönswetter and Schneeweiss 2009;Surina et al 2009;Shuka et al 2010Shuka et al , 2012Meyer 2011;Lakušić et al 2013;Bogdanović et al 2014) and disjunct localities of rare species have been discovered (Biel and Tan 2010;Barina et al 2013;Frajman et al 2013Frajman et al , 2014. A few phylogenetic studies accompanied with dating analyses have shown that many Balkan endemics originated in the Tertiary (e.g.…”
Section: Introductionmentioning
confidence: 96%
“…Several new species have been described recently (e.g. Niketić and Stevanović 2007;Schönswetter and Schneeweiss 2009;Surina et al 2009;Shuka et al 2010Shuka et al , 2012Meyer 2011;Lakušić et al 2013;Bogdanović et al 2014) and disjunct localities of rare species have been discovered (Biel and Tan 2010;Barina et al 2013;Frajman et al 2013Frajman et al , 2014. A few phylogenetic studies accompanied with dating analyses have shown that many Balkan endemics originated in the Tertiary (e.g.…”
Section: Introductionmentioning
confidence: 96%
“…Several new species have been described from the Balkans in the last decade (see Frajman et al 2014 for a review), and several new localities of rare or overlooked species have been discovered (e.g. Frajman and Schönswetter 2008;Mullaj et al 2010;Frajman and Bačič 2011;Milanović et al 2011;Barina et al 2011Barina et al , 2013Frajman et al 2013;Frajman et al 2014). Last but not least, an ever increasing number of phylogenetic and phylogeographic (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Between 2004 and 2013 ca 100 populations of the genus were studied in Albania , Barina et al 2009, 2013; their vouchers are deposited in BP. Revisions of the Chamaecytisus material, including type specimens, have been made using specimens from the following herbaria (abbreviations follow Thiers 2008+): BP, BEO, BEOU, KRA, KRAM, KW, PR, PRC, SO, SOM, W, WU and the collection of University of Tirana (Tirana, Albania; abbreviated here as TIR); additionally, we consulted with the digital collections of the following herbaria: B-W, FR, GOET, HAL, P. Barina, sp.…”
Section: Methodsmentioning
confidence: 99%